Impacts of COVID-19 on conservation programs and research activities in Nepal - Uttam Babu Shrestha; Bibek Raj Shrestha; Shirish Maharjan; Uma Dhungel; Sujata Shrestha; Babu Ram Lamichhane; Bharat Babu Shrestha (Global Ecology and Conservation, 2023)
The COVID-19 pandemic has had diverse impacts on global poverty, food security, and biodiversity conservation. While reports have highlighted both positive and negative effects of COVID-19 on biodiversity worldwide, the negative impacts have, in general, outweighed the positive ones. Despite initial reports and anecdotal evidence, there is a notable absence of country-specific empirical research assessing the COVID-19 impacts on biodiversity conservation. We documented the COVID-19 impacts on Nepal’s conservation sector by analyzing the trends of tourist visitation and revenues in Nepal’s protected areas, examining the progress on conservation programs at national and individual protected area levels, evaluating research and conservation activities, and recording the experiences of conservation practitioners. Our results, based on two online surveys and reviews of the government documents showed that the pandemic has had adverse effects on nature-based tourism, particularly leading to a significant reduction in visitation numbers to the protected areas. Furthermore, the progress of conservation programs and actions, and research activities in Nepal also suffered. Nevertheless, government agencies have maintained impressive progress in the planned activities. Protected area authorities continued to carry out critical conservation activities even during lockdowns, and most of the affected activities were resumed once the lockdowns were lifted. The study’s result is critical in mitigating the impacts of global crises such as COVID-19 on protected areas and in enhancing their resilience for the future.